Adverse Events Induced by PD-1/PD-L1 Inhibitors: A Real-World Single-Centre Experience with a Management-Based Approach - Grimaud F; Penaranda G; Stavris C; Retornaz F; Brunel V; Cailleres S; Pegliasco H; Le Treut J; Grisoni V; Coquet E; Chiche L; Rognon A (Dove Medical Press, 2021)
Fabien Grimaud,1 Guillaume Penaranda,2 Chloé Stavris,3 Frédérique Retornaz,3 Véronique Brunel,4 Sylvie Cailleres,4 Hervé Pegliasco,5 Jacques Le Treut,5 Vincent Grisoni,6 Emilie Coquet,1 Laurent Chiche,3 Amélie Rognon1 1Department of Pharmacy, Hôpital Européen, Marseille, France; 2Department of Biostatistics, Hôpital Européen, Marseille, France; 3Department of Internal Medicine, Hôpital Européen, Marseille, France; 4Department of Haemato-Oncology, Hôpital Européen, Marseille, France; 5Department of Pulmonology, Hôpital Européen, Marseille, France; 6Department of Urology, Hôpital Européen, Marseille, FranceCorrespondence: Amélie RognonDepartment of Pharmacy, Hôpital Européen, 6 Rue Désirée Clary, Marseille, 13003, FranceTel +33 4 13 42 73 00Fax +33 4 13 42 76 80Email a.rognon@hopital-europeen.frAim: To assess the efficacy and tolerance of programmed death-1 (PD-1) and PD-ligand 1 (PD-L1) inhibitors and the impact of a standardised management-based protocol in a real-world setting.Patients and Methods: Data from patients who had received anti-PD-(L)1 were collected from our pharmacy database. Clinical response and toxicity were assessed using RECIST criteria and CTCAE version 5.0, respectively. Overall survival (OS) and progression-free survival (PFS) were estimated with the Kaplan-Meier method. Potential prognostic factors were identified using Cox's model.Results: A total of 196 patients and 201 lines of treatment were included (median age: 66 (range: 38- 89) years). Types of cancer included non-small cell lung cancer (73%), transitional cell carcinoma (10%), renal cell carcinoma (6%), small cell lung cancer (5%), head and neck squamous cell carcinoma (4%) and classical Hodgkin's lymphoma (1%). Twenty-five (12%) patients had pre-existing autoimmune conditions. Our standardised management-based protocol included 129 (64%) patients. Objective response rate was 29%, median OS was 10 months (IQR: 7- 15) and median PFS was 5 months (IQR: 1- 22). Patients with an abnormal baseline complete blood count had a worse OS (HR=2.48 [95% CI: 1.24- 4.96]; p=0.0103). Thirty-three (16%) patients experienced severe (grade 3 or 4) immune-related adverse event (irAE). There were three (1%) irAE-related deaths. AEs resolved faster when patients were assessed by an internist before anti-PD-(L)1 initiation (p=0.0205).Conclusion: PD-1 and PD-L1 inhibitors are effective and safe in a real-world setting. Implementation of a standardised management-based protocol with internal medicine specialists is an effective way to optimise irAE management.Keywords: immunotherapy, elderly, PD-1 inhibitor, PD-L1 inhibitor, PDL-1 inhibitor, safety, immune-related adverse events, solid tumours, prognostic biomarkers